2021
DOI: 10.3390/vaccines9101096
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Following Immunization Associated with the First and Second Doses of the ChAdOx1 nCoV-19 Vaccine among Healthcare Workers in Korea

Abstract: As worldwide large-scale inoculation of novel vaccines is on the way, the importance of real-world data on safety cannot be overemphasized. We aimed to investigate the adverse events following immunization (AEFIs) associated with the ChAdOx1 nCoV-19 vaccine among healthcare workers (HCWs). We investigated the systemic and local adverse events reported within seven days following the first and second doses of vaccination, using the mobile vaccine adverse events reporting system (MVAERS) developed by our hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 15 publications
4
12
1
3
Order By: Relevance
“…This is supported by another study conducted in Korea where the pain, injection site tenderness, and fatigue were the top adverse events of health professionals experienced. 32 It is also supported by findings of other studies on health professionals from Togo, 31 and Nepal. 34 Compared to other brands of COVID-19 vaccines, ChAdOx1 had a lower AEFI than Moderna (94%) but higher AEFI than Pfizer vaccine (53%).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This is supported by another study conducted in Korea where the pain, injection site tenderness, and fatigue were the top adverse events of health professionals experienced. 32 It is also supported by findings of other studies on health professionals from Togo, 31 and Nepal. 34 Compared to other brands of COVID-19 vaccines, ChAdOx1 had a lower AEFI than Moderna (94%) but higher AEFI than Pfizer vaccine (53%).…”
Section: Discussionsupporting
confidence: 69%
“…On the other side, the magnitude of AEFI was lower than web-based study findings from Korea where more than 90% of the health professionals reported at least one AEFI. 32 This might be due to variations of outcome ascertainment techniques. Accordingly, the Korean study was a mobile-based daily report from the participants while we collected the data from the respondents a week after they took the vaccine, which may lead to missing mild symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The most common local side effects in this study was injection site pain (39%), followed by arm pain (25.4%), and injection site swelling (2.5%) and itching (2.5%). However, these side effects emerged generally with low frequencies than previously reported, especially with the adenoviral vector vaccines, i.e., AZD1222 where injection site pain was reported with a prevalence higher than 58% ( 24 , 27 , 47 49 ). Similarly, a large-scale multinational study covering more than 10,000 vaccinees in the Arab countries reported that more than 58% of the participants suffered from injection site pain and swelling ( 50 ).…”
Section: Discussionmentioning
confidence: 69%
“…The local and systemic side effects were more prevalent after the second dose than the first dose for both inactivated and adenoviral vector vaccines, thus, confirming what was previously reported in different studies ( 45 , 46 ). Contrarily, Omeish et al 2021 in Jordan and Jeon et al 2021 in Korea found that side effects were more frequent and more severe after the first dose ( 18 , 47 ).…”
Section: Discussionmentioning
confidence: 97%
“…Severe post-vaccination adverse events were present in 0.25% (n = 9) of our population, in which ChAdOx1-S and Gam-COVID-Vac were more likely to develop such events. A previous report on 1954 healthcare workers showed a 0.4% (n = 9) severe post-vaccination adverse incident leading to hospital attendance; BIBP-CorV (n = 1), Gam-COVID-Vac V (n = 3), and ChAdOx1-S (n = 5) [21]. Overall, among vaccine recipients, adverse events were rare and non-lifethreatening.…”
Section: Discussionmentioning
confidence: 83%